(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
An Architectural Biography is a personal life story. It may be the biography of an architect, or the story of an architectural idea – even that of a single house. It can be the history of a city, from its geological formation to the latest event happening in town. When we think of architecture as “an ethnic domain” (Langer Feeling and Form 1953) then it is a community of dwelling in a place. Biography might be the transformation of a given place in time, or at a specific moment, or a Foundation Myth: “the primitive hut”. Romulus plowed a ditch to encircle Rome. Gold was discovered in the American River. Biography is story-telling.